Increased left ventricular torsion in hypertrophic cardiomyopathy mutation carriers with normal wall thickness - Marcus Tim J; Knaapen Paul; Germans Tjeerd; Brouwer Wessel P; Rüssel Iris K; van der Velden Jolanda; Götte Marco JW; van Rossum Albert C (Journal of Cardiovascular Magnetic Resonance, 2011)
Abstract Background Increased left ventricular (LV) torsion has been observed in patients with manifest familial hypertrophic cardiomyopathy (HCM), and is thought to be caused by subendocardial dysfunction. We hypothesize that increased LV torsion is already present in healthy mutation carriers with normal wall thickness. Methods Seventeen carriers with an LV wall thickness <10 mm, and seventeen age and gender matched controls had cardiovascular magnetic resonance (CMR) cine imaging and tissue tagging. LV volumes and mass were calculated from the cine images. LV torsion, torsion rate, endocardial circumferential strain and torsion-to-endocardial-circumferential-shortening (TECS) ratio, which reflects the transmural distribution in contractile function, were determined using tissue tagging. Results LV volumes, mass and circumferential strain were comparable between groups, whereas LV ejection fraction, torsion and TECS-ratio were increased in carriers compared to controls (63 ± 3% vs. 60 ± 3%, p = 0.04, 10.1 ± 2.5° vs. 7.7 ± 1.2°, p = 0.001, and 0.52 ± 0.14°/% vs. 0.42 ± 0.10°/%, p = 0.02, respectively). Conclusions Carriers with normal wall thickness display increased LV torsion and TECS-ratio with respect to controls, which might be due to subendocardial myocardial dysfunction. As similar abnormalities are observed in patients with manifest HCM, the changes in healthy carriers may be target for clinical intervention to delay or prevent the onset of hypertrophy.